OECD Anti-Bribery Policy and Structural Differences Inside the EU - Michal Paulus; Eva Michalikova (Charles University in Prague, Institute of Economic Studies (IES), 2016)
We propose a novel application of a gravity model of trade as a policy preference mapping tool that reveals areas of potential interest groups formation. We examine a hypothesis that the EU.s inability of the coordinated anti-corruption effort is caused by its internal heterogeneity in preferences towards the anti-corruption policy. We focus only on anti-corruption effort against bribery in foreign transaction which is reflected in the effectiveness of the enforcement of the OECD anti-bribery convention. Using the gravity model, we estimate and compare preferences of western, eastern and Mediterranean EU members towards the enforcement of the convention. In addition to aggregate exports we estimate the model on disaggregated data and examine preferences across trading sectors and identify those industries which would support or oppose the anti-corruption policy. To analyse the hypothesis, we estimate a micro-founded augmented gravity model for bilateral exports of 131 countries within period 1995-2013. The results reveal significant differences between western and eastern EU members when the eastern countries are much more motivated to oppose the policy and to form a strong interest group also on the EU level. However, there are specific sectors which have potential to form a coalition towards the policy across all country groups. We have found out that the country origin (country group to which it belongs) is much better predictor of the policy preferences than exporting sector.
Keywords: F14; F42; F51; F53; F55; O17; 330; gravity model; OECD anti-bribery convention; international conflict; policy preference mapping; EU heterogeneity